2007
DOI: 10.1097/mph.0b013e318159a545
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Assessment in Acute Lymphocytic Leukemia Survivors: Role of Cranial Radiotherapy?

Abstract: Leptin has been hypothesized to play a role in the development of obesity in leukemia survivors, particularly those who have received cranial radiotherapy. This cross-sectional study evaluated the relationship between leptin levels and body mass index (BMI) in a sample of 26 acute lymphocytic leukemia survivors of both sexes, treated with and without cranial irradiation, aged 7.6 to 17 years, at a mean 3.4+/-2.0 years off treatment. There were significantly more males among the irradiated group (P<0.001), even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 26 publications
2
19
2
1
Order By: Relevance
“…The Childhood Cancer Survivor Study showed that the influence of CRT on the increase in BMI in ALL survivors was more evident in females exposed to CRT. To date, few patients in the present study were currently considered obese by means of BMI analysis (2 males, 8.3% of the ALL male subjects versus 13.8% from the Childhood Cancer Survivor Study at the age of 18-24 years) [3], which is in accord with other studies that have not found obesity in survivors of ALL by employing measures of BMI, despite the rebound of adiposity [8,9,37]. …”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…The Childhood Cancer Survivor Study showed that the influence of CRT on the increase in BMI in ALL survivors was more evident in females exposed to CRT. To date, few patients in the present study were currently considered obese by means of BMI analysis (2 males, 8.3% of the ALL male subjects versus 13.8% from the Childhood Cancer Survivor Study at the age of 18-24 years) [3], which is in accord with other studies that have not found obesity in survivors of ALL by employing measures of BMI, despite the rebound of adiposity [8,9,37]. …”
Section: Discussionsupporting
confidence: 74%
“…These alterations could lead to body fatness and metabolic derangements, both of which are factors that are suggested to contribute to features of the metabolic syndrome in this group of patients [2,4-6,11-14]. However, other factors that interact with the disease and/or therapy, such as individual host and genetic characteristics, may moderate and influence adiposity and metabolic derangements in this group of patients [3,7,8]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations